The great moderation in international capital flows: a global phenomenon? - Peter McQuade; Martin Schmitz (European Central Bank (ECB), 2016)
This paper highlights a recent `great moderation' in global capital flows, characterised by smaller volumes and lower volatility of cross-border transactions. However, there are substantial differences across countries and regions which we analyse by comparing the level of international capital flows observed in 2005-06, immediately prior to the onset of the global financial crisis, to the post-crisis period of 2013-14, when global flows arguably settled at a `new normal'. We find that since the pre-crisis period, gross capital inflows recovered more for economies with smaller pre-crisis external and internal imbalances, lower per capita income, improving growth expectations, a less severe impact of the global financial crisis and less stringent macroprudential policy. On the asset side, countries with a more accommodative monetary policy, a milder impact of the crisis and oil exporters managed to increase gross capital outflows in the post-crisis period.
Keywords: F15; F21; F32; 330; external imbalances; global financial crisis; international capital flows; monetary